2015
DOI: 10.7150/jca.11238
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of ADAM23, CDKN2A (P16), MMP14 and VIM Associated with Giant Cell Tumor of Bone

Abstract: Though benign, giant cell tumor of bone (GCTB) can become aggressive and can exhibit a high mitotic rate, necrosis and rarely vascular invasion and metastasis. GCTB has unique histologic characteristics, a high rate of multinucleated cells, a variable and unpredictable growth potential and uncertain biological behavior. In this study, we sought to identify genes differentially expressed in GCTB, thus building a molecular profile of this tumor. We performed quantitative real-time polymerase chain reaction (qPCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“… 17 Additionally, several researches stated that VIM expression was downregulated in well‐differentiated endometrial cancer cells and giant cell tumor of bone. 18 , 19 Overexpression of VIM promotes migration, invasion, and metastasis of CRC cells. 20 To our knowledge, miRNA play its biological function by suppressing target gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 Additionally, several researches stated that VIM expression was downregulated in well‐differentiated endometrial cancer cells and giant cell tumor of bone. 18 , 19 Overexpression of VIM promotes migration, invasion, and metastasis of CRC cells. 20 To our knowledge, miRNA play its biological function by suppressing target gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Battaglia et al have proved that VIM intermediate filaments are essential for the plasticity of mesenchymal cells under normal physiological conditions and cancer cell migration during epithelial–mesenchymal transition 17 . Additionally, several researches stated that VIM expression was downregulated in well‐differentiated endometrial cancer cells and giant cell tumor of bone 18,19 . Overexpression of VIM promotes migration, invasion, and metastasis of CRC cells 20 .…”
Section: Discussionmentioning
confidence: 99%
“…They showed that high expression of MAP2K3 was significantly correlated with CA125 level (p < 0.001), tumor size (p = 0.001), lymph node metastasis (p = 0.008), depth of myometrial invasion (p < 0.001), and FIGO stage (p < 0.001), indicating MKK3 as a poor prognostic biomarker [54]. Conceicao et al, conducted immunohistochemical staining on 24 samples of giant cell tumors of bone and normal tissues and reported higher expression of the MKK3, MMP14, TIMP2, and VIM genes in tumor than the normal counterpart, suggesting their involvement in invasion and metastasis [55]. With the tissue microarray (TMA) performed in a cohort of 189 colorectal cancer patients, our study identified MKK3 as a poor prognostic marker, correlating significantly high MKK3 staining with short overall survival (OS) in late-stage CRC patients [1].…”
Section: Discussionmentioning
confidence: 99%
“…The CDKN2A gene also known as p16INK4 is thought to help suppress tumors (Foulkes et al 1997). The CDKN2A protein is critical for inhibiting cell cycle progression, and the down-regulation of p16 could lead to increased cell proliferation and may contribute to the pathogenesis of several cancers (Conceição et al 2015). In a study by Chen Z et al, they analyzed CDKN2A levels in 33 tumors and found that CDKN2A may be a promising prognostic biomarker with potential molecular mechanisms to in uence the survival outcomes of cancer patients (Chen et…”
Section: Molecular Dockingmentioning
confidence: 99%